Nitrogen use and agronomic efficiency of rainfed wheat in permanent beds as affected by N fertilizer, precipitation and soil nitrate. (12th April 2021) - Limon-Ortega, Agustin
Abstract: Nitrogen (N) fertilizer is an input that has played an important role in grain yield, N use efficiency (NUE), and agronomic efficiency (AE) that needs to be studied on rainfed wheat grown in permanent beds as a planting system. The objective of this study was to test the effect of N treatments on yield, NUE and AE from 2005 to 2009. The experimental design consisted of three N rates (25, 50 and 75 kg/ha) and four N timing treatments (two single basal applications and two splits), plus a control plot (0 N). Results showed that N rate and N timing treatments had no effect on grain yield, but years, meanwhile Year–N rate interaction affected NUE and AE. Precipitation and post-harvest soil N-NO3 were identified as factors to test the years' effect on yield, NUE and AE. Regression procedures showed that the effect was greater for 25 kg N/ha treatment. The relationships between these variables and precipitation were positive, whereas the opposite occurred with soil N-NO3 . NUE and AE, however, showed negative values in crop seasons with moisture constraints from precipitation (<335 mm) and soil N-NO3 (>90 kg N-NO3 /ha). This result indicated that N removal and yield in these years were larger in control plots (0 N) than fertilizer application. Precipitation and soil N-NO3, rather than N treatments, explained most of the yield, NUE and AE variation over years. Therefore, to enhance that effect of weather and soil, further research on alternate N sources is needed.